Technical Training Junior Tennis Players Aged 8-9 as a Constituent Part of Successful Playing Activity - Inna Horodynska; Yuri Grabovskyi; Svitlana Stepaniuk; Oleg Kuznetsov (Lesya Ukrainka Volyn National University, 2018)
This article is dedicated to the issue of determining technical aptitude for playing activities in junior tennis players during the beginner stage of their sports training. The research aim is to determine the aptitude of junior tennis players aged 8-9 to proceed to the «green» level as the result of technical aptitude and competitive activities analysis. Work Results. The level of training junior tennis players has been analyzed, which consists of 3 levels (red, orange and green), each of them having their specifics in playing activities. This promotes gradual training junior tennis players for technical and tactical training. The average indices of technical training junior tennis players are determined and the correlation between technical training and competitive activity in junior tennis players are analyzed. The analysis of the correlation between the results of technical training and competitive activity has confirmed that all the criteria of technical training have the positive correlation which indicates the direct proportionality in the determined factors. Conclusions. As a result of our experimental research, based on the analysis of technical training and competitive activity of the junior tennis players, we have determined that the junior tennis players aged between 8 and 9 are ready to proceed to the «green» level of tennis.